Evaluación de los costos económicos totales de los desastres naturales: inundación en la ciudad de Sheffield, 2007 - Mendoza Tinoco, David; Méndez Delgado, Alba Verónica (El Colegio de México A.C., 2018)
Natural disasters impose high costs that lead to economic imbalances. Losses from initial physical damage generate indirect costs that amplify the total damage. This paper proposes a methodology based on Input Output modelling to evaluate the total economic costs of disasters, and analyses the case of the 2007 floods in Sheffield, UK. The results suggest that each unit of cost for direct damages, derived from the physical destruction by the flood, generates an additional cost of 0.75 units in indirect costs, counted as the loss of production caused by the disturbances along the productive chains. The analysis provides more comprehensive information on the effects of natural disasters on the economy, as well as the most affected productive sectors. This could contribute to a better allocation of resources for the risk management of natural disasters.